2022
DOI: 10.35848/1347-4065/ac647e
|View full text |Cite
|
Sign up to set email alerts
|

Novel technology of high-aspect-ratio etch utilizing coverage-controllable atomic layer deposition

Abstract: We demonstrated a coverage-controllable sidewall protective film by controlling the degree of oxidation during plasma-enhanced SiO2 atomic layer deposition (ALD) as a novel technology to suppress bowing in a high-aspect-ratio-contact (HARC) hole etch process. By depositing SiO2 protective film with atomic order on only the top-local region of patterns, to suppress bowing was achieved during HARC etch without the shrinkage of the bottom critical dimension (CD) and etch-stop. In addition, we investigated the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Such a large-scale evolution of the deposition profile and film properties was predicted within a short calculation time considering the effect of the pre-process, such as plasma etching. In addition, an etch/depo/etch sequential process for the HAR pattern 5) can be simulated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a large-scale evolution of the deposition profile and film properties was predicted within a short calculation time considering the effect of the pre-process, such as plasma etching. In addition, an etch/depo/etch sequential process for the HAR pattern 5) can be simulated.…”
Section: Methodsmentioning
confidence: 99%
“…1) Moreover, advanced complex structures and vertical integration, including fin-type field-effect transistors (FinFET), 2) vertical tunnel FETs, 3) and gate-all-around FETs, 4) have been proposed. Therefore, careful deposition process control [5][6][7][8][9][10][11][12][13][14][15][16][17] for the realization of a high-aspect-ratio (HAR) pattern to consider the coverage and film properties (density, passivation, adhesion, etc. ), both of which greatly affect the device performance, is vital.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polymer buildup on the mask and profile can lead to striation of the profile sidewalls due to uneven polymer build-up under the subsequent high-power HAR etch step. 24) Recently, Kumakura et al 27) reported applying coverage-controlled atomic layer deposition (ALD) silicon oxide film to reduce the profile bowing in HAR contact hole etching. While the use of ALD SiO 2 film to protect sidewalls is effective in some process regions, the low selectivity of sidewall passivation to the dielectric film may present some limitations in HAR ONON channel hole applications.…”
Section: Deco Carbon Liner Approachmentioning
confidence: 99%
“…32,33 This control, along with the low-pressure deposition environment, allows for the coating of high aspect ratio or geometrically complex features, such as microwires or foams, without the line of sight restrictions imposed by other coating techniques such as sputtering or flamespray. [34][35][36][37] ALD has been used to synthesize electrocatalysts or thermal catalysts on supports for CO 2 reduction. 38,39 With respect to plasma catalysis, ALD has primarily been used as a method for applying catalysts developed for pollutant degradation and non-oxidative methane coupling.…”
Section: Introductionmentioning
confidence: 99%